2011
DOI: 10.1111/j.1440-1681.2011.05535.x
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of nitric oxide synthase uncoupling by sepiapterin improves left ventricular function in streptozotocin-induced diabetic mice

Abstract: 1. Uncoupling of nitric oxide synthase (NOS) has been implicated in the pathogenesis of left ventricular (LV) dysfunction in diabetes mellitus. In the present study, we investigated the role of NOS uncoupling in oxidative/nitrosative stress and LV dysfunction in the diabetic mouse heart. 2. Diabetes was induced in wild-type (WT), endothelial (e) NOS knockout (eNOS(-/-)), inducible (i) NOS knockout (iNOS(-/-)) and neuronal (n) NOS knockout (nNOS(-/-)) mice by streptozotocin (STZ) treatment. 3. In the diabetic h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
33
0
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 43 publications
(25 reference statements)
3
33
0
2
Order By: Relevance
“…In contrast, heart rate was significantly smaller in the eNOS Ϫ/Ϫ mice than the WT mice at baseline and after sham surgery. These hemodynamic differences are consistent with the previous study using the same genotypes of mice (24). Although heart rate and blood pressures did not significantly change after MI in the WT and iNOS Ϫ/Ϫ mice, blood pressures significantly decreased after MI in the eNOS Ϫ/Ϫ mice compared with baseline and the time-matched WT and eNOS Ϫ/Ϫ mice with Table 1.…”
Section: Resultssupporting
confidence: 91%
“…In contrast, heart rate was significantly smaller in the eNOS Ϫ/Ϫ mice than the WT mice at baseline and after sham surgery. These hemodynamic differences are consistent with the previous study using the same genotypes of mice (24). Although heart rate and blood pressures did not significantly change after MI in the WT and iNOS Ϫ/Ϫ mice, blood pressures significantly decreased after MI in the eNOS Ϫ/Ϫ mice compared with baseline and the time-matched WT and eNOS Ϫ/Ϫ mice with Table 1.…”
Section: Resultssupporting
confidence: 91%
“…Although we did not measure BH 4 in the present study, the increase in NO x , an index for NO generation, and the decrease in nitrotyrosine, an index for peroxynitrite generation, in hearts that received sepiapterin suggests that oral administration of sepiapterin inhibited NOS uncoupling. These findings are consistent with our previous studies (18,37) demonstrating that sepiapterin is an effective tool in inhibiting NOS uncoupling and increasing the bioavailability of NO.…”
Section: Discussionsupporting
confidence: 82%
“…Rats were randomized to receive oral administration of sepiapterin (10 mg·kg Ϫ1 ·day Ϫ1 ) together with or without N-nitro-L-arginine methyl ester (L-NAME; Sigma Chemical, St. Louis, MO), a nonselective inhibitor of NOS, at a dose of 100 mg·kg Ϫ1 ·day Ϫ1 for 8 wk immediately after TAC (protocol A) or between 8 and 16 wk after TAC (protocol B). We chose sepiapterin at a dose of 10 mg·kg Ϫ1 ·day Ϫ1 because our previous studies (18,37) demonstrated that this dose of sepiapterin is effective in increasing the BH4-to-BH2 ratio in the mouse heart. Additional rats were randomly assigned to receive oral administration of MPG (100 mg·kg Ϫ1 ·day Ϫ1 ) for the same duration as described above.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, NOS uncoupling and tetrahydrobiopterin deficiency contribute to the inflammatory and abnormal cytokine milieu in the vasculature (71). Furthermore, hyperglycemia significantly elicits the expression of cytokine-inducible NOS (iNOS) both in vitro and in vivo (36,118). Indeed, hyperglycemia induced by streptozotocin in Nos2 gene knockout mice led to diabetic cardiomyopathy, and sepiapterin, an inhibitor of NOS uncoupling, improved systolic FIG.…”
Section: Inflammation and Oxidative Stress In Endothelial Dysfunctionmentioning
confidence: 99%